Analisis Perbandingan Kompleksitas Waktu Algoritma Mst Dalam Penyusunan Jaringan Pipa Air Bersih - Wirakusuma, Kadek Ardy; Diatmika, Kadek Doni (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The availability of clean water is the top priority for the survival of the community. Therefore, efforts are needed to distribute clean water evenly, including by building a pipeline network that reaches every house in an area. The Drinking Water Supply and Sanitation System Management Group (KPSPAMS) of Ulakan Village, Karangasem Regency, built a water pipeline network to overcome the problem of lack of clean water experienced by local residents, especially during the dry season. However, development is still often not optimal because there is a pipe rotation (circuit) that causes the length of the pipe not to be optimized and the overall cost to be higher. Thus, the preparation of an efficient and effective pipeline network is the main focus. The location studied is part of Ulakan Village, Manggis District, Karangasem Regency. This study aims to find the most optimal pipeline network arrangement through a comparison of three Minimum Spanning Tree (MST) algorithms, namely the Kruskal, Prim and Sollin algorithms. This study represents the pipeline graph into an edge list. Furthermore, with the three algorithms, the list is analyzed based on the complexity of time and computer programs to find the Minimum Spanning Tree (MST). This research seeks to provide a practical solution of the comparison of the three algorithms with a focus on theoretical understanding and experimental results.